CREM Alpha Enhances IL-21 Production in T Cells In Vivo and In Vitro - Ohl, Kim; Wiener, Anastasia; Lippe, Ralph; Schippers, Angela; Zorn, Carolin; Roth, Johannes; Wagner, Norbert; Tenbrock, Klaus (Frontiers in Immunology, 2016)
The cAMP responsive element modulator alpha (CREMα) plays a role in autoimmunity and in particular in systemic lupus erythematosus. CREMα negatively regulates IL-2 transcription and activates IL-17 expression by direct transcriptional mechanisms. To understand the role of CREM in autoimmunity we recently generated a mouse with a transgenic overexpression of CREMα selectively in T cells. This mouse is characterized by enhanced IL-17 and IL-21 expression. We herein dissect the transcriptional mechanisms of enhanced IL-21 transcription in these mice. T cells of CREMα transgenic mice display an enhanced binding of CREMα to the CD3 ζ chain promoter resulting in decreased CD3 ζ chain expression. This is accompanied by a decreased excitation threshold and enhanced Ca2+ influx resulting in Il-21 promoter activation upon T cell stimulation. Furthermore, CREMα directly binds to a CRE half-site within the Il-21 promoter which also results in enhanced promoter activity shown by promoter reporter assays. IL-21 transcription is critical for IL-17 generation in these mice, since IL-21 receptor blockade downregulates IL-17 transcription to wildtype levels. Finally, this is of functional relevance since CREMα transgenic mice display enhanced disease activity in dextrane sodium sulfate induced colitis accompanied by higher local IL-21 expression. Thus we describe 2 novel mechanisms of CREMα dependent IL-21 transcription. Since T cells of SLE patients are characterized by enhanced IL-21 transcription this might also be of functional relevance in humans.